(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Non-governmentalorganizations (NGOs) are now recognized as key third sector actors on thelandscapes of development, human rights, humanitarian action, environment, andmany other areas of public action, from the post-2004 tsunami reconstructionefforts in Indonesia, India, Thailand,and Sri Lanka,to the 2005 Make Poverty History campaign for aid and trade reform anddeveloping country debt cancellation. As these two examples illustrate, NGOsare best-known for two different, but often interrelated, types of activity –the delivery of services to people in need, and the organization of policyadvocacy, and public campaigns in pursuit of social transformation.